Crossroads—Drug Testing as Symbolic Managerial Action: In Response to “A Case Against Workplace Drug Testing” - Cavanaugh, J. Michael; Prasad, Pushkala (Organization Science, 1994)
In contrast to much of the management and organizational literature supporting drug testing (Coombs and Coombs 1991, Cowan 1987, Harris and Heft 1992), Debra Comer's (1994) "A Case Against Workplace Drug Testing" presents a refreshing series of arguments against this practice. Comer (1994) carefully scrutinizes and summarizes a substantial body of empirical and conceptual literature on workplace drug testing, on the basis of which, she makes a compelling argument against it. Comer even suggests that frequently, drug testing can have adverse consequences for organizations in terms of hurting employee morale, productivity and performance. For the most part, we are in agreement with Comer's findings. However, we suggest that her paper falls short of offering a convincing explanation for the continued use of drug testing in the workplace. Her case against drug testing is marshalled from two distinct vantage points: (1) normative, and (2) instrumental. Both are incomplete when it comes to explaining the prevalence of workplace drug testing. In the remainder of this paper, we explain why we think these two perspectives are inadequate, and suggest an alternative way of looking at the phenomenon.